Location Based Attendance Tracking Using Mobile Devices - Sharma, A; Jain, VB (International Journal of Computer Sciences and Engineering, 2025)
This paper focuses on the automation of the mundane process of attendance tracking using the location determination capabilities of a modern day smartphone. The idea is to use the Global Positioning System (GPS), Wireless Fidelity (Wi-Fi) and Network signals to determine the location of the mobile device with the desired accuracy. We then determine a suitable threshold to determine a radius from the fixed location (the place of work perhaps), within which if the device is present, the bearer of the device is considered to be present at work. The aim of this system is to automate the archaic and mundane process of recording attendance without the necessity of any additional hardware requirements other than a smartphone. Attendance recording has come across a handful of make-overs up until now, and the most successful system seems to be the Radio-Frequency Identification (RFID) based access control cards which need to be held in front of a reader at the place of work. This system relies on the additional hardware requirement of the RFID enabled card and a reader, dependencies which, we aim to eliminate.this paper focuses on the automation of the mundane process of attendance tracking using the location determination capabilities of a modern day smartphone. The idea is to use the Global Positioning System (GPS), Wireless Fidelity (Wi-Fi) and Network signals to determine the location of the mobile device with the desired accuracy. We then assign a suitable threshold to calculate a radius from the fixed location (the place of work perhaps), within which if the device is present, the bearer of the device is considered to be present at work.